Effectiveness of Hydrotherapy Interventions for Students with Aquaphobia: A Systematic Review and Meta-Analysis - Santoso, Januar Abdilah; Santoso, Puji (FKIP - Universitas Riau, 2025)
This systematic review examines the effectiveness of hydrotherapy interventions for students with aquaphobia across educational settings. Despite the importance of water safety skills, aquaphobia remains a significant barrier to swimming competence among students worldwide. A comprehensive analysis of peer-reviewed studies (2018-2025) was conducted using PRISMA guidelines. Electronic databases (PubMed, ERIC, PsycINFO, Web of Science, Scopus) were searched to identify studies examining hydrotherapy interventions for school-aged participants with aquaphobia. Studies were included if they used experimental or quasi-experimental designs, reported quantitative outcomes, and focused on educational settings. Meta-analysis using random-effects models was conducted to calculate pooled effect sizes. Results showed that mindfulness-integrated hydrotherapy demonstrated highest effectiveness (g = 0.96), followed by cognitive-behavioral hydrotherapy (g = 0.83), adaptive aquatic programs (g = 0.79), virtual reality-assisted exposure (g = 0.72), and graded exposure therapy (g = 0.66). Interventions were most effective for younger children (5-8 years) and longer programs (≥12 weeks). These findings provide evidence-based recommendations demonstrating that mindfulness-integrated and cognitive-behavioral approaches are most effective for students with aquaphobia in educational settings.